1995
DOI: 10.1063/1.470333
|View full text |Cite
|
Sign up to set email alerts
|

Effective core potential studies of lanthanide complexes

Abstract: A recently developed compact effective core potential (ECP) scheme for lanthanides [T. R. Cundari and W. J. Stevens, J. Chem. Phys. 98, 5555 (1993)] is applied to molecular species—the lanthanide trihalides (LnX3, Ln=Ce to Lu; X=F, Cl, Br, I). This research is the first ECP study of lanthanide trihalides in which 4f electrons are explicitly included in the lanthanide valence space. The high-spin 4fn configuration of Ln(III) is described using multiconfiguration (MC) and unrestricted Hartree-Fock (UHF) wave fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 29 publications
7
48
1
Order By: Relevance
“…Full geometry optimization and vibrational analysis of PrBr 3 were carried out, and the equilibrium structure and six normal coordinates Q i 's were obtained as shown in Figure 4. The optimized bond lengths of Pr-Br and the symmetry were 5.20 (Bohr) and D 3h , respectively, in good agreement with previously obtained results by Cundari et al 47 This bond length is also in reasonable agreement with a recent theoretical one, 5.15 (Bohr) with CASPT2, 48 and with the experimental one, 35 5.08 (Bohr). The frequency of each normal vibration, as shown in Table 4, is also in reasonable agreement with the experimental one.…”
Section: Oscillator Strengths Of Lanthanide Trihalidessupporting
confidence: 93%
“…Full geometry optimization and vibrational analysis of PrBr 3 were carried out, and the equilibrium structure and six normal coordinates Q i 's were obtained as shown in Figure 4. The optimized bond lengths of Pr-Br and the symmetry were 5.20 (Bohr) and D 3h , respectively, in good agreement with previously obtained results by Cundari et al 47 This bond length is also in reasonable agreement with a recent theoretical one, 5.15 (Bohr) with CASPT2, 48 and with the experimental one, 35 5.08 (Bohr). The frequency of each normal vibration, as shown in Table 4, is also in reasonable agreement with the experimental one.…”
Section: Oscillator Strengths Of Lanthanide Trihalidessupporting
confidence: 93%
“…[5,6,7,8,9] Recent advances in quantum chemistry have provided a complementary and independent tool to probe molecular properties of lanthanide halide compounds. [10,11,12,13,14,15] All calculations so far reported agree in predicting a pyramidal equilibrium structure for the isolated LnF 3 molecules with a very shallow minimum, in agreement with most of the molecularbeam electric deflection data. [16] Recently, we showed that for the LnF 3 ·IG and LnF 3 ·IG 2 (IG = Ne, Ar, Kr, Xe and N 2 ) model complexes, LnF 3 -IG interactions are strong, and a possible LnF 3 planar structure may be found in contrast to the results on isolated molecules.…”
supporting
confidence: 83%
“…Calculations at B3LYP/ECP D ,MIDIX and MP2/ECP D ,MIDIX levels (see Table 4) overestimate essentially the equilibrium distances r e (Ln-I) as compared with the experimental values. Despite using the ECP s [20] which does not include 4f-electrons into the core, the MCSCF/ ECP s ,CEP s d calculations [21] also resulted in overestimated values. Basis set ECP D ,MIDIX augmented by polarization functions 3f2g [13] for Ln atom improves the results for both, MP2 and B3LYP, methods and led to the r e (Ln-I) values which are very close to the experimental r g -values.…”
Section: Parameters Of Thermal-averaged Configurationmentioning
confidence: 92%